TEKNIK YANG EFEKTIF UNTUK MENUMBUHKAN KEMAMPUAN BERBICARA SISWA DI SEKOLAH DASAR - Elfa Santika (Universitas Sulawesi Tenggara, 2024)
This study aims to explore effective techniques in improving elementary school students' speaking ability. Good communication is an important skill that supports students' academic success and social-emotional development. Through a literature study method, this study analyzes various techniques such as role-playing methods, storytelling techniques, group discussions, and project-based learning (PBL). This study discusses various learning techniques in improving elementary school students' speaking ability and the role of teachers as facilitators, motivators, and mediators in the process. The findings of the study indicate that the implementation of these techniques effectively encourages students to be more active in speaking, increases their self-confidence, and develops their communication skills. In addition, an interactive learning environment and moral support from teachers play an important role in motivating students to practice speaking regularly. With the right and sustainable strategies, students' speaking ability can be significantly improved, preparing them to communicate better in various academic and social situations.